Does clean cooking energy improve mental health? Evidence from China. (July 2022) - Liu, Pihui; Han, Chuanfeng; Teng, Minmin
Abstract: Existing studies that evaluate the impact of cooking with solid fuels on human beings understate the negative effect on mental health. This paper attempts to fill this gap by investigating the impact of cooking energy transition on depression and the cognitive abilities of middle-aged and elderly people. Base on a large panel data set from China, we applied several complementary methods—propensity score matching, "difference-in-differences", and fixed-effect model to overcomes the challenges of treatment selection bias and unobserved time-invariant heterogeneity that might have prevented us from identifying the causal effect. Depression outcomes and cognitive ability are measured by the Center for Epidemiological Studies Depression Brief Scale (CES-D) and a series of high-quality cognitive tests, respectively. The results reveal that cooking energy transition can significantly reduce the CES-D index and the rate of depression and improve cognitive reasoning ability in the middle-aged and elderly but has no significant impact on cognitive memory ability. Moreover, the effect is more salient for certain groups, such as females, rural residents, southern residents and middle-income families. Finally, potential pathways through which cooking energy transition affects mental health, including physical health, social activities, labour participation and medical expenditures, are discussed. Highlights: We focus on the impact of cooking energy transition on depression and cognitive. A several complementary methods was applied to solve the endogeneity problem. Cooking energy transition can significantly improve mental health of the elderly. Cooking energy transition can improve mental health in direct and indirect ways.